HUBUNGAN KONSUMSI KACANG-KACANGAN (SUMBER PHYTOESTROGEN) DENGAN USIA MENOPAUSE - Sri Muljati; Susie Suwarti; Heryudarini Harahap; Titus Priyo Harjatmo; Komari Komari; Sandjaja Sandjaja; Amelia Amelia (Persagi, 2003)
PHYTOESTROGEN CONSUMPTION AND MENOPAUSEBackground: Health development increase the life expectancy age on women. The life expectancy on women in 1980 was 50.9 years, which was Increase to 62.7 years in 1995. Due to decline of estrogen level, the menopause often get menopause syndrome. The impact of low estrogen level could decrease the bone mass (osteoporosis). Phytoestrogen could be deriving menopause syndrome in women. Isoftavone is one of phytoestrogen compound and has anti oxidant. Bean, e.g. soybeans as phytoestrogen sources were consumption in great quantity in Indonesia. Objectives: The study was conducted to examine the relationship between bean as phytoestrogen sources and menopause aged.Methods: The study was cross-sectional that was done in Tanah Datar (West Sumatra) and Bantul (Yogyakarta). Respondents were 360 women who had menopause. Food consumption was collected by Food Frequency Questioner (FFQ) and menopause age was interviewed by asking the women history. Results: Soybean and its products e.g. Tempe, tofu as well as bean, e.g. kidney bean, 'tolo bean' are phytoestrogen sources that often are eaten by the menopause women in both area. The average of isoflavon consumption of women that had menopause aged > 50 years higher than women that had menopause aged 50 years. Conclusions: Women that consumed less phytoestrogen had higher risk of early menopause. Phytoestrogen could be obtained from nuts as well as it's product e.g soybean, tempe, tofu. Recommendations: Women naturally have a high risk suffering from osteoporosis therefore they are suggested to consume beans as (a one way) to prevent early menopause. The promotion of bean advantages could be done through PUGS approach.Keywords: menopause, phytoestrogen, soybeans